Theology and identity - K. Lamak (Acta Theologica)
In this book, Kwame Bediako explores the theme of identity and Christianity from a broad perspective, addressing many issues modern scholars have battled with. Although Bediako’s focus is postmissionary Christianity in Africa, dating from the 1960s to the present, he gives a foundational background to issues related to culture and identity since the birth of Christianity in the first century AD.